Minimizing DNA trapping while maintaining activity inhibition via selective PARP1 degrader - Li Chen; Yahui Zou; Renhong Sun; Mei Huang; Xiaotong Zhu; Xiao Tang; Xiaobao Yang; Dake Li; Gaofeng Fan; Yu Wang (Cell Death and Disease, 2024)
Abstract Poly (ADP-ribose) polymerase 1 (PARP1) catalyzes poly (ADP) ribosylation reaction, one of the essential post-translational modifications of proteins in eukaryotic cells. Given that PARP1 inhibition can lead to synthetic lethality in cells with compromised homologous recombination, this enzyme has been identified as a potent target for anti-cancer therapeutics. However, the clinical application of existing PARP1 inhibitors is restrained by side effects associated with DNA trapping and off-target effects, highlighting the need for improved therapeutic strategies. By integrating protein degradation technology, we synthesized a PROTAC molecule 180055 based on the Rucaparib junction and VHL ligand, which efficiently and selectively degraded PARP1 and inhibited PARP1 enzyme activity without a noticeable DNA trapping effect. Furthermore, 180055 kills tumor cells carrying BRCA mutations with a minor impact on the growth of normal cells both in vitro and in vivo. This suggests that 180055 is a PARP1-degrading compound with excellent pharmacological efficacy and extremely high biological safety that deserves further exploration and validation in clinical trials.